Pulp Response following Direct Pulp Capping with Dentin Adhesives and Mineral Trioxide Aggregate; An Animal Study - Akhavan, Ali; Arbabzadeh, Farahnaz; Bouzari, Majid; Razavi, Sayed Mohammad; Davoudi, Amin (Iranian Endodontic Journal, 2017)
Introduction: Pulp vitality and its continuous dentin prodution are essential for long-term success of direct pulp capping (DPC). The aim of present study was to evaluate the histopathological response of the canine pulp following DPC using either different dentin adhesive resins (DAR), calcium hydroxide (CH) or mineral trioxide aggregate (MTA). Methods and Materials: DPC was done on 72 dog’s teeth using 6 types of dental materials (n=12) (4 types of DAR, white MTA and CH). Therefore, six healthy dogs were anesthetized and 2 teeth from each dog were allocated to either type of mentioned DPC agents. The dental pulps were exposed mechanically by drilling in the center of class V cavities. The different types of capping materials included DARS (Clearfil S3 Bond, Optibond FL, Single Bond and Clearfil SE Bond), white MTA and CH. After 7, 21 and 63 days, two dogs were euthanized in each interval. Microscopic evaluations were done according to following criteria: intensity of inflammation, presence of necrosis and formation of hard tissue. The recorded data were analyzed by the Kruskal-Wallis, Friedman, Cochran’s and Fisher’s exact tests using SPSS software version 12 at significant level of 0.05. Results: No significant differences were found regarding necrosis among DPC materials (P>0.05). However, MTA caused higher amount of hard tissue formation after 63 days in comparison with 21 days. Conclusion: MTA provided the highest degree of hard tissue formation after 63 days. However, further studies should be performed for administering a definitive material. Keywords: Dentin Adhesive Systems; Direct Pulp Capping; Mineral Trioxide Aggregate